Modulation of Cyclones With Tropical and Extratropical Origins by Mesoscale SSTs in the Kuroshio Extension Region. Issue 4 (22nd February 2023) - Zhang, Xingzhi; Ma, Xiaohui; Ma, WeiWei; Wu, Lixin; Liu, Qinyu; Zhang, Li; Wang, Baiping
Abstract: Two typical classes of cyclones originating from the tropics (ToCs) and extratropics (EoCs) with distinct preconditions, and passing the Kuroshio Extension (KE) region in cold season in the North Pacific are detected and tracked based on high‐resolution atmospheric simulations with and without mesoscale sea surface temperature (SST) forcing. A comparison between ToC‐to‐mesoscale SST and EoC‐to‐mesoscale SST responses indicates that the different cyclone development and the environmental water vapor restoration in the KE are primarily attributed to different ToC and EOC's preconditions. The higher initial intensity of ToCs leads to stronger atmospheric response to mesoscale SSTs and extended cyclone growth whilst the colder and drier precondition of EoCs induces stronger water vapor restoration in the KE after EoCs passing‐by. It is further demonstrated that the water vapor restoration is dominated by moisture convergence. The study provides new insights into the physical understanding of mesoscale SSTs' influence on cyclogenesis in the midlatitudes. Plain Language Summary: The active forcing of mesoscale sea surface temperatures (SSTs) associated with oceanic fronts and eddies on the atmosphere in the midlatitude has been well documented. Existing studies also demonstrated the effect of mesoscale SSTs on cyclogenesis, emphasizing the role of moist processes. However, it is still not clear how the preconditions of cyclones will affect the cyclogenesis and restoration of water vapor in response to mesoscale SSTs. Focusing on two typical classes of cyclones originating from the tropics (ToCs) and extratropics (EoCs) and passing the Kuroshio Extension (KE) region in cold season in the North Pacific, we found that the preexisting intensity, moisture and temperature differences between ToCs and EoCs can influence the strength, timing, location of cyclone response to mesoscale SSTs. Moreover, the drying and cooling effect of EoCs on the background creates less stable atmospheric conditions, favorable for environmental water vapor restoration in the KE after cyclones passing‐by. The study provides further understandings on how the precondition affect the interaction between mesoscale oceanic processes and cyclone development in the midlatitudes. Key Points: The higher wind precondition of tropical originated cyclones causes stronger cyclone responses to mesoscale sea surface temperature and extended cyclone growth The colder and drier precondition of extropical originated cyclones causes stronger environmental moisture restoration in the Kuroshio